Airtel Zero : data pricing, two sided markets led business models and net neutrality - Sahay, Arvind, (SAGE Knowledge. Cases., 2015)
It was June 2015 and the Airtel office in New Delhi needed to come to a decision soon. Two months earlier, Shyam Mardikar, Chief of Strategy at Bharti Airtel, had opined that "the Internet, I believe, was neutral, is neutral and will be neutral. There is absolutely no agenda, no direction, no industry force coming in the way." He was speaking at an industry conference in the aftermath of the launch of "Airtel Zero" that adopted a data pricing approach that, many said, violated the principle of net neutrality.